THE RELATIONSHIP BETWEEN LANGUAGE LEARNING AND MOTIVATION - Sultanov Bektosh Ochilovich (Western European Studies, 2024)
This article examines the relationship between language learning and motivation. We often use the term "motivation" in lessons to help students achieve the intended goal of the lessons. Terms such as “motivation” and “motivate students” are the most commonly used words in teachers' vocabulary. In addition, the terms “motivation” and “motivator” have already become popular in the business circles of our country. However, in this article we would like to discuss the importance of motivation in learning foreign languages. We all know that knowing a foreign language helps anyone increase their chances of achieving their goals. Although the problem of increasing student motivation is relevant for every subject, it is especially relevant when learning a foreign language. Motivation is therefore considered as the main driving force in learning a foreign language, the motives of which relate to the subjective world of the individual and are determined by his internal motives
Keywords: Learning motivation; language learning strategies; motivational power